Scrutinizing the Malaysian regulatory framework on Shari’ah advisors for Islamic financial institutions - Hassan, Rusni; Hussain, Mohammad Azam (IIUM Institute of Islamic Banking and Finance, 2013)

(untitled)
Islamic banking, takaful and Islamic Capital Market are the main component of Islamic financial system in Malaysia. Shari’ah compliance is one of the attributes to distinguish Islamic Financial Institutions (IFIs) from its counterpart. Adherence to Shari’ah principles is fundamental to the operations of IFIs and such adherence is a continuing process as long as such institutions operate. The Shari’ah Advisors appointed by the IFIs are responsible in ensuring the Shari’ah compliance of IFIs in carrying out its Islamic financial business. The requirement for the appointment of Shari’ah Advisors in IFIs has been included in the statutes governing IFIs as well as guidelines and circulars issued by authoritative bodies related to Islamic banking, takaful and Islamic Capital Market. This indicates that, the appointment of Shari’ah Advisors in IFIs is a vital to the industry. A specific regulatory framework on Shari’ah Advisors is essential in regulating their duties and responsibilities as may be in ensuring that the operations of IFIs conform to Shari’ah principles. Furthermore, a strong regulatory framework on Shari’ah Advisors is one of the factors in ensuring the resilience development of Islamic finance industry. Henceforth, this study seeks to analyze the Malaysian regulatory framework on Shari’ah advisors as their significant roles and responsibilities in ensuring Shari’ah compliance of IFIs.